Strategi Pengembangan Ecotourism Pulau Derawan Kabupaten Berau Kaltim - Policharpus Raja Peta (Samarinda State Polytechnic, 2019)
The ecotourism potensial is very interested becouse the island montioned to have tourism potential is tourism culture and tourism nature. Get data with used of description technique research and qualitative technique research. From research proceeds about the ecotourism management to experience negative impact of tourism inviromental. Like a rubbish and too more facilities, becouse the level international tourist visited from 2010 years till to 2011 years down proceeds. But the domestic tourist still stable